An estimation technique in agile archetype using story points and function point analysis. (2017) - Dhir, Saru; Kumar, Deepak; Singh, V.B.
Agile approach is responsible to bring out the high quality of deliverable in a shorter period. It has been observed that existing development methods do not focus on the early stages of estimation of size, cost, effort and time due to uncertainty in requirements. In this paper, an estimation model using agile methodologies has been proposed, so that a development process can be estimated from the initial stage to the delivery of the project. This paper also proposes a new algorithmic approach and is compared with an existing algorithmic approach. Further, this paper discusses the implementation of a project according to the proposed estimation model and new algorithmic approach. At the end of the paper, a comparison between existing and proposed model, strengths and its implications of proposed model have been discussed.